The potency of quality incentives: Evidence from the Indonesian dairy value chain - Treurniet, Mark (Agricultural and Applied Economics Association, 2021)
Misalignment of quality incentives along value chains may limit quality and therefore function as a barrier to smallholder participation in modern value chains. This article uses survey and administrative data to study how individual quality incentives provided by private actors can help smallholders to improve milk quality. By matching farmers on baseline characteristics, I find that individual quality incentives increased the compositional quality of milk quickly after its introduction. Together with physical inputs and training, individual quality incentives also increased the hygienic quality of milk. Decreasing hygienic quality over time by treated farmers suggests that the impact of the intervention decreased over time.